2015
DOI: 10.3390/ijms160714395
|View full text |Cite
|
Sign up to set email alerts
|

Ginsenoside Rd Protects SH-SY5Y Cells against 1-Methyl-4-phenylpyridinium Induced Injury

Abstract: Ginsenoside Rd (GSRd), one of the main active monomer compounds from the medical plant Panax ginseng, has been shown to promote neuronal survival in models of ischemic cerebral damage. As an extending study, here we examined whether GSRd could exert a beneficial effect in an experimental Parkinson disease (PD) model in vitro, in which SH-SY5Y cells were injured by 1-methyl-4-phenylpyridinium (MPP+), an active metabolic product of the classical Parkinsonian toxin1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(30 citation statements)
references
References 32 publications
1
27
0
Order By: Relevance
“…Akt phosphorylates its downstream substrate glycogen synthase kinase-3β (GSK-3β), which leads to inactivation of the enzyme. GSK-3β dysregulation plays an important role in the pathogenesis of many neurodegenerative diseases, including Parkinson's disease [32][33][34] . Alterations in GSK-3β activity have been shown to contribute to DA neuronal death induced by MPTP and other insults.…”
Section: Dhm Protects Da Neurons From Mpp + Toxicity and Inhibits Thementioning
confidence: 99%
“…Akt phosphorylates its downstream substrate glycogen synthase kinase-3β (GSK-3β), which leads to inactivation of the enzyme. GSK-3β dysregulation plays an important role in the pathogenesis of many neurodegenerative diseases, including Parkinson's disease [32][33][34] . Alterations in GSK-3β activity have been shown to contribute to DA neuronal death induced by MPTP and other insults.…”
Section: Dhm Protects Da Neurons From Mpp + Toxicity and Inhibits Thementioning
confidence: 99%
“…MtDNA copy number was considered as a surrogate marker of mitochondrial function [37]. Liu et al demonstrated that ginsenoside Rd, one of the active components of Panax ginseng , was able to reduce intracellular ROS levels, enhance antioxidant enzymatic activities, stabilize the mitochondrial membrane potential, and increase intracellular ATP levels [38]. Kim et al also found that ginsenoside Rg3 increased ATP levels in C2C12 myotubes and enhanced the expression of key genes involved in mitochondrial biogenesis such as NRF-1, TFAM, and peroxisome proliferator-activated receptor γ coactivator 1α (PGC-1α) which is a key regulator that induces mitochondrial biogenesis by activating other transcription factors [39].…”
Section: Discussionmentioning
confidence: 99%
“…5D), which may indicate these compounds have no selective affinity for the target cells. Ginsenosides Rg 1 [79], Rb 1 [9,10], and Rd [11] have been found to protect SH-SY5Y cells, and Ro was shown to have a neuroprotective effect in animal experiments, but only Rd and Ro were verified in this work. Our experiments do not defy the pharmacological effects of the reported ginsenosides in the literature, and they may exert effects through other pathways.…”
Section: Resultsmentioning
confidence: 71%
“…Recent studies have suggested Panax ginseng has a wide range of beneficial effects on aging, central nervous system disorders, and neurodegenerative diseases [25]. Panax ginseng extract [6], ginsenosides Rg 1 [79], Rb 1 [9,10], and Rd [11] have been found to protect SH-SY5Y cells against 1-methyl-4-phenylpyridinium-induced injury. In our preliminary experiments, ginseng extracts and the ginsenosides fractions were found to be capable of facilitating the proliferation of SH-SY5Y cells and protecting the cells against H 2 O 2 -induced injury.…”
Section: Introductionmentioning
confidence: 99%